The abnormal phosphorylation of the Rac1, Lim-kinase 1, and Cofilin proteins in the pathogenesis of Hirschsprung's disease. Issue 4 (1st April 2022) - Zhou, Wan-Kang; Qu, Yan; Liu, Yuan-Mei; Gao, Ming-Juan; Tang, Cheng-Yan; Huang, Lu; Du, Qing; Yin, Jia
ABSTRACT: Rac1 can affect the migration of neural crest cells by regulating the polymerization of actin and the membrane formation process. But the role of the Rac1 signaling pathway in the pathogenesis of Hirschsprung's disease (HSCR) remains unclear. In order to investigate the mechanism of the abnormal protein phosphorylation of Rac1, Lim-kinase 1 (Limk1) and Cofilin involved in the pathogenesis of HSCR. The protein phosphorylation levels of these proteins were detected by Western blot in 30 samples of HSCR narrow segment, 30 samples of transitional segment tissues, and 14 samples of normal intestinal tissues. Subsequently, in the SH-SY5Y human neuroblastoma cell line, a Rac1, Limk1, and Cofilin inhibitor group, a Rac1 overexpression group (PDGF-BB group), a Rac1 overexpression group + a Limk1 inhibitor group (P-B group), a Rac1 overexpression group + a Cofilin inhibitor group (P-C group) were established. The results showed that the expressions of p-Rac1, p-Limk1, and p-Cofilin in HSCR narrow segment and transitional segment were lower than those in normal intestine (p < 0.05). The expression levels of p-Rac1, p-Limk1, and p-Cofilin in the relative inhibitor group were significantly lower than those in the control group (p < 0.05), and the proliferation and migration levels in the control group and Rac1 overexpression group were significantly higher than those in the Rac1, Limk1, and Cofilin inhibitor group (p < 0.05). In conclusion, the decreased phosphorylation of the Rac1/Limk1/Cofilin signaling pathway in HSCR could inhibit the proliferation and migration of SH-SY5Y cells, and this might be associated with the pathogenesis of HSCR. Graphical Abstract: uf0001